Alternative access for transcatheter aortic valve replacement in older adults: A collaborative study from France and United States. Issue 6 (3rd July 2018) - Damluji, Abdulla A.; Murman, Magdalena; Byun, Seunghwan; Moscucci, Mauro; Resar, Jon R; Hasan, Rani K.; Alfonso, Carlos E.; Carrillo, Roger G.; Williams, Donald B.; Kwon, Christopher C.; Cho, Peter W.; Dijos, Marina; et al.
Abstract: Background: We examined the outcomes of older adults undergoing nontrans‐femoral (non‐TF) transcatheter aortic valve replacement (TAVR) procedures including trans‐apical (TA), trans‐aortic (TAo), trans‐subclavian (TSub), and trans‐carotid (TCa) techniques. Methods and Results: This is an observational study of all consecutive older patients who underwent non‐TF TAVR for symptomatic severe AS with Edwards Sapien (ES), Medtronic CoreValve, ES3 or Lotus Valve at three centers in France and the United States from 04/2008 to 02/2017. Baseline characteristics and clinical outcomes were defined according to VARC‐2 criteria. Of 857 patients who received TAVR, 172 (20%) had an alternative access procedure. Of these, 45 (26%) were TA, 67 (39%) TAo, 17 (10%) TSub, and 43 (25%) TCa procedures. The preference for non‐TF access site was different between the two countries (US: TA 39%, TAo 52%, TSub 9%; TCa 0% vs. France: TA 9%, TAo 23%, TSub 11%, and TCa 57%, P‐ value < .001). Most patients who underwent TAo TAVR were older women (median age: TA 82, TAo 84, TSub 81, TCa 81, P‐ value = 0.043; female gender: TA 32 (27%), TAo 30 (55%), TSub 10 (41%), TCa 27 (37%), P‐ value = .021). The predicted Society of Thoracic Surgery risk of mortality was similar among groups (TA 7%, TAo 7%, TSub 6%, TCa 7%, P‐ value= .738). No differences were observed in the frequency of para‐valvular leak, intra‐procedural bleeding, vascular complications, conversion to open‐heart surgery, or development of acute kidney injury. The highest in‐hospital mortality was observed in the TAo group (TA 2%, TAo 15%, TSub 0%, TCa 2%, P‐ value = .014). However, hospital length of stay, one‐month, and one‐year mortality were similar among non‐TF techniques. Conclusion: Although regional differences exist in the choice of alternative access techniques, centers with high technical expertise can provide a safe alternative to traditional TF TAVR. TAo TAVR was associated with higher in‐hospital mortality than other non‐TF approaches, and this may have reflected patient rather than procedural factors. All alternative access techniques had similar mortality rates and clinical outcomes at one‐year follow‐up. Trans‐carotid access is safe and feasible compared to other non‐TF access techniques.